Mediasi dalam Perspektif Teori Penegakan Hukum Goldstein - Fattaah, Abdul (WELFARE STATE Jurnal Hukum, 2023)
Law enforcement is basically divided into two types, litigation and non-litigation. Law enforcement by means of litigation is defined as law enforcement within the court mechanism, while for non-litigation it is considered as law enforcement outside the court. Currently, there is a shift in perspective from the public who are starting to resolve their legal issues in a non-litigation way, namely mediation. Goldstein's Law Enforcement Theory offers three types of law enforcement. The question then is what is meant by Goldstein's Law Enforcement Theory and mediation seen from the perspective of Goldstein's Law Enforcement Theory. This paper is of a juridical-normative type which uses a literature approach in its preparation. The conclusion is that Goldstein's Law Enforcement Theory divides law enforcement into three types:Total enforcement; Full enforcement; Actual enforcement. Furthermore, mediation will not eliminate the essence of law enforcement, it's just that in mediation, it must be limited what actions can be resolved by mediation in order to maintain public order